Port of Cotonou and accessibility of landlocked ECOWAS contrises to the international market. - PADONOU, Vodoungnon Anignikin; ALLAGBE, SOTONDJI BENJAMIN; TAMBA, Jean Gaston (My University, 2021)
The port plays a key role in serving landlocked countries in general and those in the ECOWAS region. The port of Cotonou is a hub that serves as an interface between the northern countries and the ECOWAS hinterlands by facilitating the import of manufactured goods and the export of local and mining products. The overall objective of this study is to analyse the contribution of the port of Cotonou to the free trade area of the ECOWAS region. Documentary research, direct observation and field surveys are the techniques used to collect the data. The questionnaire addressed to economic operators, concessionary port operators, transporters, and drivers. Thus, two hundred and ninety-five (295) socio-professional actors in the field of transport, port and maritime were surveyed. The results showed that Benin’s economy is dependent on foreign trade (90%) which is carried out through port and maritime activities. The study reveals that, in terms of trade integration, almost all EU countries have an above-average score, except Benin (0.474), Niger (0.467) and Guinea-Bissau (0.307). Most maritime and port actors interviewed admitted that more than 71% of the flow of goods through the port of Cotonou is destined for the consumer and distribution markets of the Sahel countries, especially the Republic of Niger. Services have been put in place in several structures to improve and accelerate the fluidity and speed of transit. Certainly, efforts remain to be undertaken to make the port of Cotonou more competitive in the West African row to capture more customers from landlocked countries.
Keywords: Port of Cotonou; ECOWAS; Accessibility; Landlocked countries; International market